Shear strength of steel fiber reinforced concrete deep beams without stirrups - Birincioglu, Mustafa I.; Keskin, Riza S. O.; Arslan, Guray (TECHNO-PRESS, 2022)
Concrete is a brittle material and weak in tension. Traditionally, web reinforcement in the form of vertical stirrups is used in reinforced concrete (RC) beams to take care of principal stresses that may cause failure when they are subjected to shear stresses. In recent decades, the potential of various types of fibers for improving post-cracking behavior of RC beams and replacing stirrups completely or partially have been studied. It has been shown that the use of steel fibers randomly dispersed and oriented in concrete has a significant potential for enhancing mechanical properties of RC beams. However, the studies on deep steel fiber reinforced concrete (SFRC) beams are limited when compared to those focusing on slender beams. An experimental program consisting of three RC and nine SFRC deep beams without stirrups were conducted in this study. Besides, various models developed for predicting the ultimate shear strength and diagonal cracking strength of SFRC deep beams without stirrups were applied to experimental data obtained from the literature and this study.
Keywords: deep beam; reinforced concrete; shear strength; steel fiber; BEHAVIOR; STRUT; Construction & Building Technology; Engineering; Materials Science